Von der partizipativen Forschung zum Empowerment. Eine methodologische Bestimmung kollaborativer Autoethnografie - Vochatzer, Stefanie; Schorr, Sophia; Lieb, Daniel; Stange, Leah; Kamenik , Anna Maria (Partizipative Forschung und Empowerment - Erkundungen in Feldern der Sozialen Arbeit)

"...da gerade hier die allgemeinen Theorieen uns nur zu oft im Stiche lassen." Rousseau in der Kritik gelehrter Frauen seiner Zeit - Vochatzer, Stefanie; Engelman , Sebastian ("Nicht die Wahrheit wird anerkennt" - Mathilde Vaerting (1884-1977) Deutungen, Ordnungen und Tradierungen in der Erziehungswissenschaft)

Erziehung zur Hausfrau und Mutter? Geschlechterspezifische Umbrüche in der Mädchenerziehung des 18. Jahrhunderts - Vochatzer, Stefanie (Stand, Beruf(ung), Geschlecht - Umbrüche und Transformationsprozess im gesellschaftlichen und kulturellen Wandel)

Rezension zu: Wasmuth, Helge; Sauerbrey, Ulf; Winkler, Michael: Finding Froebel. The Man Who Invented Kindergarten. New York 2023 - Vochatzer, Stefanie (H-Soz-Kult)

Der Briefroman als Medium weiblicher Kritik in der Aufklärung – Einblicke in Caroline Rudolphis »Gemälde weiblicher Erziehung« - Vochatzer, Stefanie (»Debattieren, Opponieren, Protestieren – Interdisziplinäre Perspektiven auf sprachliche Praktiken des Widersprechens«)

Connection and Community - Vochatzer, Stefanie (Creative Approaches to Climate and Peace Education. An Educationr’s Guide to Using Storytelling and Art)

Crossing Boundaries: Autoethnography of Subjective Experiences During Meditation - Kothe, Anna-Katharina; Vochatzer, Stefanie; Oesterle, Christian; Ruf, Steffen Philipp (The Qualitative Report)
In this autoethnographic quadrologue, the authors aim to show how meditation experiences defy verbalization in a qualitative research setting. This leads to the insight that an autoethnographic approach may be a much better fit for such an experience, where complex and inexpressible things can be found. This is especially the case since autoethnographic texts include and immerse the reader in the experience. Even though in the case of meditation this can hardly be achieved, this quadrologue aims at conveying some of the struggles and peculiarities of meditation practice. It focuses on the research process leading to the decision to employ an autoethnography paradigm. Thus, the focus of this article is the differentiation of autoethnography from other methodological approaches and the conscious decision in favour of this method, which is rather unusual in German-speaking countries. The authors develop the thesis that both the meditation experience and the decision to employ an autoethnographic paradigm led to the experience of “wandering off the beaten track” and crossing the boundaries of what is usually done in society and social science respectively.

Fortbildung to go: Twitter als Ratgeber für Lehrkräfte - Vochatzer, Stefanie; Schröder, Sarah; Fischer, Christian
Keywords: Lehren Digitale Medien Bildungsforschung Weiterbildung Lehrkraft Social Media Förderung

Caroline Rudolphis „Gemälde weiblicher Erziehung“. Einblicke in die Mädchenerziehung der Spätaufklärung - Vochatzer, Stefanie (POSITIONEN)

Autoethnografie und Kreatives Schreiben - Vochatzer, Stefanie; Engelmann , Sebastian (Journal der Schreibwissenschaft)

Lehrideale und ihre Rolle in der (Ver-)Achtung der Pädagogik - Vochatzer, Stefanie (Friedrich Wilhelm Dörpfeld Lehrerideale im 19. Jahrhundert)

Das Ich im Schatten der Methode. Eine Hinführung zum Potenzial autoethnograﬁschen Schreibens für die wissenschaftliche Praxis - Vochatzer, Stefanie; Engelmann, Sebastian (Journal der Schreibberatung (18) 2, S. 86–99)